POSISI DAN PERAN MEDIA DALAM KEHIDUPAN MASYARAKAT - Husnul Khatimah (TASÂMUH, 2018)
Mass media has an important position in people's lives, so mass media is placed as mass communication which acts as a communicator and agent of change, being a pioneer of change in the public environment that can influence audiences through messages such as information, entertainment, education and other messages and accessible to the public at large. As a form of the importance of media can be seen from the influence felt by the public, starting from the cognitive, effective, to conative aspects of the mass media and the negative-positive impact of social media. Even though the position and role of the media are very important, the community must also be careful with media remember that the nature of the media is so flexible. Negative values ??of the role of the media in Indonesia can occur either from the mass media or social media, so there needs to be attention from each party, both from the media manager to the community itself. The participation of several parties in paying attention to the media is expected to filter out negative things that might occur.